Current status of colon capsule endoscopy. Issue 4 (4th September 2020) - Hosoe, Naoki; Limpias Kamiya, Kenji J. L.; Hayashi, Yukie; Sujino, Tomohisa; Ogata, Haruhiko; Kanai, Takanori
Abstract : While both the annual incidence and mortality of colorectal cancer are slowly but steadily decreasing in the United States, the incidence of such malignancy is increasing in Japan. Thus, controlling colorectal cancer in Japan is a major concern. In 2006, colon capsule endoscopy was first introduced by Eliakim et al . First‐generation colon capsule endoscopy had a moderate sensitivity for detecting polyps of more than 6 mm. Thus, second‐generation colon capsule endoscopy was developed to achieve higher sensitivity. Colonoscopy is the gold standard tool for colorectal cancer surveillance. With an improvement in the imaging function, the performance of second‐generation colon capsule endoscopy is almost as satisfactory as that of colonoscopy. Certain situations, such as incomplete colonoscopy and contraindication for use of sedation, can benefit from colon capsule endoscopy. Colon capsule endoscopy requires a more extensive bowel preparation than colonoscopy and computed tomography colonography because it requires laxatives not only for bowel cleansing but also for promoting the excretion of the capsule. Another problem with colon capsule endoscopy includes the burden of reading and interpretation and overlook of the lesions. Currently, the development of automatic diagnosis of colon capsule endoscopy using artificial intelligence is still under progress. Although the available guidelines do not support the use of colon capsule endoscopy for inflammatory bowel disease, the possible application of colon capsule endoscopy is ulcerative colitis. This review article summarizes and focuses on the current status of colon capsule endoscopy for colorectal cancer screening and the possibility for its applicability on inflammatory bowel disease.